(untitled) (Perner’s Contacts, 2017)
The paper is focused on the new structure and dividing of the European airspace and its possible future benefits. This ambitious project can change and improve travelling time in air passenger transport, of course in case of realization. At maximum load in the long run can serve multiple lines, which corresponds with the expected increase of demand for air transport. Future positive effects would be reflected in air fares and shortening waiting times at airports. Whole target is to create functional and effective system enabling cost savings. Secondly, this system will be useful for the benefit of further increasing operational safety of air transport and systematic reduction of emissions from air traffic.